Stratigraphy and structural pattern of Kebumen Region using Second Vertical Derivative of Gravity Data, Central Java - Alam, Syaiful (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
Gravity forward modeling has been carried out in Kebumen Region, Central Java Province. With its position on the mélange complex, the geological complexity in this area is still a challenge to be modeled. Bougeur anomaly values in the study area ranged from 50 mGal to 130 mGal. The structural morphology of the Luk-Ulo Mélange Complex and Kulon Progo Mountain have higher Bougeur anomaly, ranging from 105 to 125 mGal. The residual positive anomaly zones in the northwest and southeast are situated with residual negative anomaly zones in between. The shallow effect through the Second Vertical Derivative method shows the patterns of fault types separating the two anomalous zones of Karangsambung and Kulon Progo region. The Luk Ulo Mélange Complex and stratigraphy of Karangsambung Formation up to Halang Formation are faulted by thrust-fault and strike-slip structural pattern. Keyword: Stratigraphy, structural pattern, second vertical derivative.